Stem-Based Science Learning In Junior High School: Potency For Training Students’ Thinking Skill - Septian Murnawianto; Sarwanto Sarwanto; Sentot Budi Rahardjo (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2017)
STEM (Science, Technology, Engineering, and Mathematics) education including science learning, is needed to face 21st-century development, especially for training thinking skill. STEM is believed to increase students’ thinking skill, interest, and STEM literacy. This study aims to know the extent of thinking skill trained through science learning in Junior High School and to know challenges and potencies of developing STEM- based science learning. The study was conducted in SMP N 1 Masaran through various data collection methods. Data were collected by in-depth interviews with 7 science teachers, observation, documentation, and literature study about plan and process of the science lesson, also STEM education as an approach. And then, data were analysed reflectively toward various documents and literature. Assessments which categorized